OECD indicators and their implications for higher education policy in Brazil - Palavezzini, Juliana; Alves, Jolinda Moraes (Argumentum, 2020)
The purpose of this essay is to analyze the Brazilian higher education scenario, according to the Organization for Economic Cooperation and Development (OECD), with the objective of analyzing the indicators presented and pointing out the main challenges of this educational level nowadays. Analyzes three indicators expressed in the report "Education At a Glance 2018 - OECD indicators": schooling and the labor market; access to higher education and financial resources applied to education. The results show that, in Brazil, there is a strong relationship between levels of schooling, employability and income. There is low coverage of higher education, especially in the supply via public network. Even so, the OECD has recommended shifting financial investments to other levels of education, promoting the defense of technical education, which poses major challenges to higher education.Keywords: Higher education. OCDE Indicators. OCDE. Challenges.